Development of a new class of self-healing and therapeutic dental resins. (May 2019) - Wu, Junling; Xie, Xianju; Zhou, Han; Tay, Franklin R.; Weir, Michael D.; Melo, Mary Anne S.; Oates, Thomas W.; Zhang, Ning; Zhang, Qiang; Xu, Hockin H.K.
Abstract: Bulk fracture and secondary caries are the two main problems causing failures and shortening the lifetime of dental resinous restorations. This article reviews recent research on self-healing dental and biomedical materials. This includes the development of self-healing dental resin composites and adhesives, combining self-healing with calcium phosphate nanoparticles in the resins for tooth lesion remineralization, and adding antibacterial monomer into self-healing resins to suppress oral biofilm grows and acid production. Furthermore, since the oral environment experiences saliva and drinks, this paper also reviews research on the self-healing of dental resins while being submerged in an aqueous environment, and the effect of long-term water-aging time from 1 day to 6 months on the self-healing capability. The new class of materials have demonstrated excellent self-healing efficacy in various material systems including bonding agents, composites and cements. They could heal cracks, regain load-bearing ability, inhibit oral pathogens, reduce or eliminate biofilm acids, raise biofilm pH to protect the teeth, and regenerate lost tooth minerals. Furthermore, their effects were indicated to be durable and long-lasting. While most of the recent publications on self-healing dental resins are from our group, this article also reviews publications from other researchers. The novel class of dental materials with triple benefits of self-healing, antibacterial and remineralization capabilities offer the much-needed improvements to address the two main reasons for restoration failures: fracture and secondary caries. They are expected to have potential for a wide range of dental and biomedical applications to overcome the current challenges and prolong the restoration life. Highlights: This article includes the development of self-healing dental resin composites and adhesives, combining self-healing with calcium phosphate nanoparticles in the resins for tooth lesion remineralization, and adding antibacterial monomer into self-healing resins to suppress oral biofilm grows and acid production. Furthermore, since the oral environment is wet and fluid, this paper also reviews research on the self-healing of dental resins while being submerged in an aqueous environment, and the effect of long-term water-aging on the self-healing capability. While most of the recent publications on self-healing dental resins are from our group, this article also reviews publications from other researchers. The new class of self-healing dental materials have established excellent self-healing efficacy in various material systems including resins, bonding agents, composites and cements. This novel class of dental materials with triple benefits of self-healing, antibacterial and remineralization capabilities offer the much-needed improvements to address the two main reasons for restoration failures: fracture and secondary caries, furthermore, their effects were indicated to be durable and long-lasting.